Quality evaluation and functional classification of Arabic health apps: A systematic review - Asma AM Abahussin; Ahmed AA Alnakhibi; Bandar MA Alfulaij (Digital Health)
Objective The study aimed to systematically review mHealth apps available for Arabic speakers regarding quality and functional classification. Methods A systematic search was conducted on the Apple App Store. Eligible apps were downloaded and tested thoroughly and rated independently by two reviewers using the Mobile App Rating Scale (MARS). The National Institute for Health and Care Excellence (NICE) evidence standards framework for evaluating Digital Health Technologies (DHTs) was used to perform the functional classification for the included apps. Results Sixty-one health-related apps met the eligibility criteria and were included in the study. The average overall MARS score across all apps was 4.03 ( SD  = 0.38), indicating a generally high quality of the apps. The functions of the reviewed apps fit into 7 out of 10 NICE classifications. We found that 50% of the applied functions were equally split between ‘communicate’ and ‘inform’, 39% fell within the ‘self-manage’ and ‘preventive behaviour change’ classes, and only 11% of the apps were classified as having ‘treat’, ‘diagnose’ and ‘simple monitoring’ functions. Furthermore, our review indicated that 42% of the apps focused on supporting general health, and 28% covered diet and physical activity. Conclusion This work summarises the current state of available free-of-charge mHealth apps for Arabic speakers on the Apple App Store by highlighting their quality and coverage of functionalities and areas of health. In general, most of the apps were considered to be of decent quality but with partially limited functions and coverage of health conditions. Developers of future Arabic health apps should focus on engagement and aesthetic features, employing more advanced functions and supporting a wide range of health interventions.